Sodium-Glucose Cotransporter-2 Inhibitor (SGLT2i) as a Primary Preventative Agent in the Healthy Individual: A Need of a Future Randomised Clinical Trial? - Xu, Dan; Chandler, Owain; Wee, Cleo; Ho, Chau; Affandi, Jacquita S.; Yang, Daya; Liao, Xinxue; Chen, Wei; Li, Yanbing; Reid, Christopher; Xiao, Haipeng (Frontiers in Medicine, 2021)
Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are a relatively novel class of drug for treating type 2 diabetes mellitus (T2DM) that inhibits glucose reabsorption in the renal proximal tubule to promote glycosuria and reduce blood glucose levels. SGLT2i has been clinically indicated for treating T2DM, with numerous recent publications focussing on both primary and secondary prevention of cardiovascular and renal events in Type 2 diabetic patients. The most recent systematic review and meta-analysis of cardiovascular outcome trials showed that SGLT2i have moderately significant benefits on atherosclerotic major adverse cardiovascular events (MACE) that appear only in patients with established atherosclerotic cardiovascular disease.1 In this review and analysis, SGLT2i have however demonstrated clinically significant benefits in reducing hospitalisation for heart failure and worsening of renal disease regardless of existing atherosclerotic cardiovascular disease or previous heart failure history. Another meta-analysis suggests that the therapeutic beneﬁt associated with SGLT2i on both all-cause and cardiovascular mortality in EMPAREG OUTCOME study is a class effect, namely, a signiﬁcant decrease in myocardial infarction, without increased stroke risk.2 All these outcome trials recruited type 2 diabetic patients. This article aims to postulate and review the possible primary prevention role of SGLT2i in healthy individuals by reviewing the current literature and provide a prospective overview. The emphasis will include primary prevention of Type 2 Diabetes, Heart Failure, Chronic Kidney Diseases (CKD), Hypertension, Obesity and Dyslipidaemia in healthy individuals, whom are defined as healthy, low or intermediate risks patients.